Different ramp-incremental slopes elicit similar Vo2max and fatigability profiles in females and males despite differences in peak power output - Azevedo, R. D. A.; Fleitas-Paniagua, P. R.; Trpcic, M.; Iannetta, D.; Millet, G. Y.; Murias, J. M. (Journal of Applied Physiology, 2023)
The aim of this article is to investigate the effects of different ramp-incremental (RI) slopes on fatigability and its recovery in females and males. Ten females and 11 males performed RI tests with distinct slopes, in separated and randomized sessions, 15 (RI15), 30 (RI30), and 45 (RI45) W·min-1. Performance fatigability was assessed by femoral nerve electrical stimuli evoked during and after isometric maximal voluntary contraction (IMVC) of knee extensors at baseline and after task failure at min 0.5, 1.5, 2.5, 5, and 10. Maximal oxygen uptake (Vo2max) and peak power output (POpeak) were also measured. There were significant and similar declines from pre- to post-RI test in RI15, RI30, and RI45 for IMVC (-23%; -25%; -25%, respectively; P < 0.05) and potentiated single twitch (-46%; -47%; -49%; P < 0.05), whereas voluntary activation did not change (-1%; -1%; 0%; P > 0.05). There were no RI condition effects, nor time × condition interaction for IMVC, potentiated single twitch and voluntary activation (all P > 0.05). V?o2max was not different among RI15, RI30, and RI45 conditions (3.30, 3.29, and 3.26 L·min-1, respectively; P = 0.717), but POpeak was (272, 304, and 337 W, respectively; P < 0.001). Overall, performance fatigability profiles were similar between sexes after the RI tests and during recovery. In addition, during recovery, high-frequency doublets and single twitch recovered faster after RI30 and RI45 compared with RI15, regardless of sex (all P > 0.05 for sex differences). In conclusion, RI tests of different slopes that elicited similar Vo2max but different POpeak did not affect the profile of performance fatigability at task failure in females and males.